Purified Cas9 Fusion Proteins for Advanced Genome Manipulation. Issue 4 (20th March 2017) - Mircetic, Jovan; Steinebrunner, Iris; Ding, Li; Fei, Ji‐Feng; Bogdanova, Aliona; Drechsel, David; Buchholz, Frank
Abstract : The CRISPR/Cas9 system (CRISPR = clustered regularly interspaced short palindromic repeats) has rapidly become one of the most versatile genome manipulation technologies, and different methods to introduce the Cas9 nuclease activity into cells have been developed. The direct delivery of purified Cas9 protein complexed with a guide RNA as a ribonucleoprotein (RNP) has emerged as an advantageous approach, as it provides instant, but limited activity of the enzyme, thereby reducing off‐target cleavage. The usefulness of the CRISPR/Cas9 system has recently been extended by the generation of Cas9 or dead (d)Cas9 fusion genes. However, these systems have so far been mainly explored when delivered by expression plasmids. Here, a variety of purified Cas9 fusion proteins are generated, and their utility is tested in a number of assays. This work illustrates that Cas9 fused to green‐ or red‐fluorescent proteins can be usefully employed to increase the frequency of targeted cells when transfected as RNPs. Furthermore, it is demonstrated that purified dCas9 fused to a dual transactivation domain can potently activate gene expression when transfected as an RNP into embryonic stem cells. The results show that purified Cas9 fusion proteins are versatile and efficient reagents that facilitate advanced genome manipulation. Abstract : Delivery of the programmable nuclease Cas9 as a ribonucleoprotein has considerable advantages over expression‐based methods in genome editing. The generation and purification of Cas9 fusion proteins offer further improvements of the technology and accelerate the process of genome engineering. The utility of green‐ and red‐fluorescent‐protein‐tagged Cas9 and the use of a dead Cas9 fusion protein to activate gene expression are presented.